2005
DOI: 10.4028/www.scientific.net/msf.500-501.97
|View full text |Cite
|
Sign up to set email alerts
|

Microalloying of Cold-Formable Multi Phase Steel Grades

Abstract: Microalloying elements like Al, B, Nb, Ti ,V can be used to optimise the microstructure evolution and the mechanical properties of advanced high strength steels (AHSS). Microalloying elements are characterised by small additions < 0.1 mass% and their ability to form carbides or nitrides. They can increase strength by grain refinement and precipitation hardening, retard or accelerate transformations and affect the diffusion kinetics as well as the stacking fault energy. Thus, by their addition the AHSS with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 9 publications
(12 reference statements)
0
21
0
2
Order By: Relevance
“…This behaviour is due to a high Al content in the steel. The martensite start temperature (M s ) is relatively low, what favours austenite stabilization in TRIP steels [1][2][3]. Pearlite is delayed to long times and the bainitic field is left-shifted.…”
Section: Thermodynamic Equilibrium Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour is due to a high Al content in the steel. The martensite start temperature (M s ) is relatively low, what favours austenite stabilization in TRIP steels [1][2][3]. Pearlite is delayed to long times and the bainitic field is left-shifted.…”
Section: Thermodynamic Equilibrium Diagramsmentioning
confidence: 99%
“…They consist of different soft and hard structural constituents in various proportions, which enable to obtain a very wide range of mechanical and technological properties. The microstructure of dual phase (DP) steel contains soft ferrite and hard martensite whereas the multiphase microstructure of TRIP (Transformation Induced Plasticity) steel consists of ferrite, bainite and retained austenite [1][2][3][4][5][6]. New demands of the automotive industry for relatively low-cost steel sheets characterized by tensile strength above 1,000 MPa require further searching of new chemical composition strategies.…”
Section: Introductionmentioning
confidence: 99%
“…12,21,22) Besides, Al TRIP steels show very high austenite carbon content even in the beginning of IH. 21) Aforementioned results lead to the question whether enhanced ferrite growth during cooling at intermediate cooling rates can be an effective contributor to chemical as well as particle size stabilization of austenite, especially in Al steels processed under conditions of moderate cooling rate and short IHt at 460°C.…”
Section: The Role Of New Ferrite On Retained Austenite Stabilization mentioning
confidence: 99%
“…8,9,12,14,16,17) Unlike Si TRIP steels, several authors have pointed that Al TRIP steels only need moderate holding times (less than 60 s) at temperatures closer to Zn bath temperature (450-475°C) to obtain substantial amounts of RA with a remarkable stability and optimal mechanical properties. 9,12,13,15,16,[18][19][20][21] This represents an important advantage, as efforts are being made to minimize or even to omit the isothermal bainite transformation step 22) in order to approach to industrial processing conditions of CGL. On this matter, some authors found that Al can accelerate the bainite formation.…”
Section: Introductionmentioning
confidence: 99%
“…The solid solution strengthening caused by Al and Si compensates smaller C content. Sometimes, the steels contain chromium (Hamada, 2007;Mujica Roncery et al, 2010) or microadditions of Nb, Ti and B (Bleck & Phiu-on, 2005;Grajcar et al, 2009;Huang et al, 2006). Mechanical properties of high-manganese steels are dependent on structural processes occurring during cold deformation, which are highly dependent on SFE (stacking fault energy) of austenite (De Cooman et al, 2011;Dumay et al, 2007;Vercammen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%